Распределение аллелей микросателлитного локуса Xbarc55-2B, сцепленного с геном гибридного некроза Ne2, в сортах мягкой пшеницы (Triticum aestivum L.) - Галаев, А.В.; Галаева, М.В.; Сиволап, Ю.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. Identification of bread wheat varieties from different regions by Xbarc55-2В locus closely linked to gene Ne2. Methods. Polymerase chain reaction (PCR), gel-electrophoresis. Results. 257 genotypes of bread wheat varieties from Ukraine and Russia selection centers were identified by the locus Xbarc55-2В. There were detected six alleles of this locus, namely 146, 142, 136, 132, 126 and 122 bp. Allele 136 bp was met more frequently (47,5–89,5 %) in the general set of varieties and in the sets of varieties from individual regions. Allele 132 bp, which is typical for Mironovskaya 808 (variety-carrier of dominant allele of Ne2 gene), was detected in 12,5 % of the studied varieties. Conclusion. Allele 136 bp is probably associated with the recessive allele of ne2 gene.